SIRT1 mediates obesity- and nutrient-dependent perturbation of pubertal timing by epigenetically controlling Kiss1 expression. Issue 1 (December 2018) - Vazquez, M.; Toro, C.; Castellano, J.; Ruiz-Pino, F.; Roa, J.; Beiroa, D.; Heras, V.; Velasco, I.; Dieguez, C.; Pinilla, L.; Gaytan, F.; Nogueiras, R.; et al.
Abstract Puberty is regulated by epigenetic mechanisms and is highly sensitive to metabolic and nutritional cues. However, the epigenetic pathways mediating the effects of nutrition and obesity on pubertal timing are unknown. Here, we identify Sirtuin 1 (SIRT1), a fuel-sensing deacetylase, as a molecule that restrains female puberty via epigenetic repression of the puberty-activating gene, Kiss1 . SIRT1 is expressed in hypothalamic Kiss1 neurons and suppressesKiss1 expression. SIRT1 interacts with the Polycomb silencing complex to decreaseKiss1 promoter activity. As puberty approaches, SIRT1 is evicted from theKiss1 promoter facilitating a repressive-to-permissive switch in chromatin landscape. Early-onset overnutrition accelerates these changes, enhancesKiss1 expression and advances puberty. In contrast, undernutrition raises SIRT1 levels, protractsKiss1 repression and delays puberty. This delay is mimicked by central pharmacological activation of SIRT1 or SIRT1 overexpression, achieved via transgenesis or virogenetic targeting to the ARC. Our results identify SIRT1-mediated inhibition ofKiss1 as key epigenetic mechanism by which nutritional cues and obesity influence mammalian puberty. The onset of mammalian puberty is sensitive to metabolic changes and nutritional status, but the mechanisms underlying this phenomenon are poorly understood. Here the authors show that the epigenetic regulator of transcription, SIRT1, mediates the effects of under and overnutrition on pubertal timing by controlling the expression ofKiss1 in hypothalamic neurons.